Cryptanalaysia Of SVD & DWT Based Watermarking Schemes - Ting, Chai-Wen (2007)
This thesis is about the cryptanalaysis of SVD & DWT based watermarking schemes. We first analyze four SVD or DWT based robust watermarking schemes: the Ganic-Eskicioglu DWT-SVD scheme, Liu-Tan SVD scheme, Shieh et.al SVD scheme and the Liu et. al.